Impact of Shoreline Changes to the Coastal Development - Mohd Azharn, Madihah; Nizam Abdul Maulud, Khairul; Norsakinah Selamat, Siti; Firoz Khan, Md; Jaafar, Othman; Shafrina Wan Mohd Jaafar, Wan; Mastura Syed Abdullah, Sharifah; Ekhwan Toriman, Mohd; Khairul Amri Kamarudin, Mohd; Barzani Gasim, Muhammad; Juahir, Hafizan (International Journal of Engineering and Technology, 2018)
The coast zone is one of the most fragile area in Malaysia and can be affected easily due to environmental threats. This study mainly focuses on analysis impact of shoreline changes on coastal development using Geographical Information System (GIS) approach to produce geospatial visualization and identify the changes areas along Sabak Bernam to Kuala Selangor. This study evaluates the shoreline changes using topographic maps in 1993 and SPOT 5 satellite images in 2013. The major findings of this study were the highest impact that caused by erosion was from Sungai Burung to Sungai Panchang Bedena and the development that have been affected in this area for 5 years (2018) and 10 years (2023) ahead were residential area, school and aquaculture activities. However, the lowest impact of erosion was occurred from Sungai Nipah to Sungai Nibong and there was no development affected in the year 2018 till 2023. The results obtained from this study are very important for the governmentâ€™s future policy and the development strategy along coastal area and at the same time it helping in dealing with the phenomenon of sea level rise and climate change.Â Â